A new bipolar device for sealing and cutting: ex and in vivo studies for performance evaluation. Issue 8 (1st December 2022) - Thiel, Christian; Frericks, Luca T.; Schenk, Martin; Königsrainer, Alfred; Brucker, Sara Y.; Kraemer, Bernhard; Steger, Volker; Biber, Ulrich; Linzenbold, Walter; Enderle, Markus D.; Thiel, Karolin
Abstract: Introduction: A novel multipurpose bipolar radiofrequency instrument, the Erbe Dissector (EDS), which simultaneously seals and cuts tissue, was developed. Ex vivo sealing rate and time, burst pressure, jaw temperature and thermal spread were studied in porcine renal arteries. Material and methods: In vivo, 13 surgical tasks were performed in two pigs: beside sealing rate and time, overall performance in sharp and blunt dissection, tissue sticking, hemostasis, precision, etc., were evaluated by four surgeons compared with ENSEAL G2 (EG2) using surveys on a Likert scale (1 = very poor; 5 = very good). Results: Ex vivo, the EDS sealing rate was 91.7% (33/36 arteries) at an average sealing time of 2.1 s (range 1.7–2.8) and a burst pressure of 1040 ± 350 mmHg. The maximum jaw temperature was 87 ± 4 °C and the mean lateral thermal spread was 0.8 ± 0.2 mm. In vivo, the sealing rate for arteries and veins was 92.6% (50/54) and the median seal and cut time was 1.6 s (range: 1.3–2.9). The average EDS performance score across all tasks was 4.4 ± 0.6 Likert points. For five shared tasks, EDS was better than EG2 (4.4 ± 0.5 versus 3.4 ± 0.6 Likert points; p = 0.016). Conclusions: EDS seals and cuts arteries and veins rapidly with good safety and user-friendliness.